Clinical-Statistical Study On The Prevalence Of Non-Cariogenic Lesions In Adults - Ali Ahmed Obeyah; Z. Ibrahim Al-Shami; A. Mohamed Al-Labani; Oana Adina Armencia (Romanian Society of Oral Rehabilitation, 2013)
Biomechanical induced dental problems affect a relatively high percent of the adult population. The aim of study was to determine the prevalence of specific lesions for dental wear. Material and method The study was conducted on a group of 300 subjects, selected from the 4th Medical Clinic of CFR Clinic Hospital, for which the criteria of including- excluding was respected. For evaluating the alteration degree, the TWI indicator was used, and for statistical analysis the SPSS17 program for Windows. Results and discussions The study highlights a mean variation of patients with wear lesions quantified according to the TWI indicator (3.096 of all patients present stage 1 affection; a mean of 3.066 with stage 2 affection; 3.01 for stage 3 and 2.8 with stage 4 affection). Conclusions There are correlations between sexes, age groups, general status, wear lesion patterns, associated lesions and their predominance.